2014
DOI: 10.1016/j.tsf.2014.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Leakage current under high electric fields and magnetic properties in Co and Mn co-substituted BiFeO3 polycrystalline films

Abstract: Co and Mn co-substituted BiFeO 3 films were prepared on Pt/Ti/SiO 2 /Si(100) substrates, and the effect of co-substitution on the structural, electric, and magnetic properties of the prepared films was systematically investigated. Cross-sectional transmission electron microscopy observations showed that the films were homogeneous; moreover, no magnetic secondary phases were observed in the films. Nano-beam energy-dispersive X-ray spectroscopy, carried out at various points in the films, revealed that Co and Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…[5][6][7][8][9] In particular, many studies concentrated on the suppression of leakage current in BFO by adopting different synthesis techniques. [10][11][12][13][14] On perusal of available literature, significant reduction in the leakage current found to have been achieved in BFO based materials. [15][16][17][18] Most reports attribute for the decreased leakage current in BFO either due to the crystalline strain or owing to oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] In particular, many studies concentrated on the suppression of leakage current in BFO by adopting different synthesis techniques. [10][11][12][13][14] On perusal of available literature, significant reduction in the leakage current found to have been achieved in BFO based materials. [15][16][17][18] Most reports attribute for the decreased leakage current in BFO either due to the crystalline strain or owing to oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…However, for pure BiFeO 3 ceramics, there are some inherent impediments to its ferroelectricity and piezoelectricity. It is difficult to synthesize pure perovskite phase BiFeO 3 due to the formation of impurities such as Bi 2 Fe 4 O 9 [6], Bi 25 Fe 4 O 39 [7], Bi 24 FeO 40 [8], and Bi 46 Fe 2 O 72 [9]. Besides, pure BiFeO 3 usually possesses high leakage current because of the reduction of Fe 3þ -Fe 2þ during sintering [10].…”
mentioning
confidence: 99%
“…Recently, it has been reported that the dielectric loss and leakage current of the BiFeO 3 -BaTiO 3 can be reduced significantly after the addition of a small amount of MnO 2 [23]. According to the previous investigations, the substitution of La 3þ [24] for Bi 3þ in BiFeO 3 can enhance the ferroelectric and magnetic properties of the ceramics while the substitution of magnetically active ions (Co 2þ , Mn 4þ ) for Fe 3þ in BiFeO 3 can tailor the ferromagnetic properties of materials [18,25]. To our knowledge, there are few reports on the ceramic with simultaneously partial substitutions of Bi 3þ (A-site) by La 3þ and Fe 3þ (B-site) by magnetic active ions Co 2þ and Mn 4þ .…”
mentioning
confidence: 99%